The Botany [of] the Antarctic voyage of H.M. discovery ships Erebus and Terror in the years, 1839-1843 : under the command of Captain Sir James Clark Ross - Hooker, Joseph Dalton, 1817-1911 (London : Reeve, [Weinheim : J. Cramer, 1847)
v. 1. Flora Antarctica. 2 pts. -- v. 2. Flora Novae-Zelandiae. 2 pts. -- v. 3. Flora Tasmonia. 2 pts. Mode of access: Internet.